Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics: Student Research Workshop 2020
DOI: 10.18653/v1/2020.acl-srw.29
|View full text |Cite
|
Sign up to set email alerts
|

AraDIC: Arabic Document Classification Using Image-Based Character Embeddings and Class-Balanced Loss

Abstract: Classical and some deep learning techniques for Arabic text classification often depend on complex morphological analysis, word segmentation, and hand-crafted feature engineering. These could be eliminated by using character-level features. We propose a novel end-to-end Arabic document classification framework, Arabic document imagebased classifier (AraDIC), inspired by the work on image-based character embeddings. AraDIC consists of an image-based character encoder and a classifier. They are trained in an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The most important technique for Arabic text classification is usually representation and classification, so in this section, we will survey the most important steps for that reason. In this section, we will conduct a brief literature review focusing on two key stages: representation such as paper [6,7] and classification such as paper [8] as follows:…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important technique for Arabic text classification is usually representation and classification, so in this section, we will survey the most important steps for that reason. In this section, we will conduct a brief literature review focusing on two key stages: representation such as paper [6,7] and classification such as paper [8] as follows:…”
Section: Related Workmentioning
confidence: 99%
“…In 2020, Daif et al presented AraDIC [6], the first deep learning framework for Arabic document classification based on image-based characters Ameur et al suggested a hybrid CNN and RNN deep learning model for categorizing Arabic text documents using static, dynamic, and fine-tuned word embedding [3]. The most meaningful representations from the space of Arabic word embedding are automatically learned using a deep learning CNN model.…”
Section: Classificationmentioning
confidence: 99%